2017
DOI: 10.2196/publichealth.7397
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Development of a Mobile Phone HIV Testing Intervention: Intentions to Use Specific HIV Testing Approaches Among Young Black Transgender Women and Men Who Have Sex With Men

Abstract: BackgroundRegular human immunodeficiency virus (HIV) testing of persons at risk is critical to HIV prevention. Infrequent HIV testing and late diagnosis of HIV infection have been observed among young black men who have sex with men (MSM) and transwomen (transgender women)—two groups overrepresented in the HIV epidemic.ObjectiveThe objective of this study was to inform the development of a brief mobile phone intervention to increase HIV testing among young black MSM and transwomen by providing a tailored recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Mobile phones can deliver programs to support behavioral change [ 1 , 2 ], data management or surveillance [ 3 , 4 ], and other essential public health activities. The use of mobile phones could potentially promote health and gender equity [ 5 , 6 ] and enhance community empowerment [ 7 , 8 ]. Short message service (SMS) text messaging, in particular, has been shown to be a simple and effective intervention for improving health service delivery in pregnant women [ 9 , 10 ], infectious disease cases [ 11 , 12 ], weight loss cases [ 13 ], and diabetes cases [ 14 ] and increasingly for smoking cessation support [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phones can deliver programs to support behavioral change [ 1 , 2 ], data management or surveillance [ 3 , 4 ], and other essential public health activities. The use of mobile phones could potentially promote health and gender equity [ 5 , 6 ] and enhance community empowerment [ 7 , 8 ]. Short message service (SMS) text messaging, in particular, has been shown to be a simple and effective intervention for improving health service delivery in pregnant women [ 9 , 10 ], infectious disease cases [ 11 , 12 ], weight loss cases [ 13 ], and diabetes cases [ 14 ] and increasingly for smoking cessation support [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Users of HIVST have the autonomy to include other individuals in their testing experience such as their partners, friends, or family members. Given the growing evidence in support of couples HIV testing among MSM, the use of HIVST with main partners is being explored in multiple studies (Koblin et al, 2017;Neme, Goldenberg, Stekler, Sullivan, & Stephenson, 2015;Stephenson, Freeland, et al, 2017;Stephenson, Suarez, et al, 2017;Sullivan, Wall, et al, 2014;Wall et al, 2016). Partners can be a source of comfort and support during the HIV testing experience and can help mitigate the emotional distress that may occur after receiving a positive test result (Martinez et al, 2014).…”
mentioning
confidence: 99%
“…Partners can be a source of comfort and support during the HIV testing experience and can help mitigate the emotional distress that may occur after receiving a positive test result (Martinez et al, 2014). Additionally, recent studies demonstrated an association between support provided by non-partner and intentions to test for HIV (Frye et al, 2015;Koblin et al, 2017).…”
mentioning
confidence: 99%
“…Questions about sexual behaviors in the prior 3 months include the number of anal or vaginal sex partners, insertive and receptive anal sex, condom use, and HIV status of partners. Questions about use of substances in the prior 3 months include marijuana, stimulants (powder cocaine, crack cocaine, methamphetamine), prescription drugs, poppers, erectile dysfunction drugs, and club drugs [ 38 ]. Presence of depressive symptoms is measured with the Patient Health Questionnaire 2 (PHQ-2) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The computerized algorithm that provides a personalized recommendation of the optimal HIV testing approach for individuals was based on the findings from a quantitative survey described previously [ 38 ]. The survey collected data on intentions to test by self-test, couples HIV testing and counseling, and at a clinic or other provider, as well as awareness and comfort levels with specific testing modalities, sociostructural factors, behavioral risk, peer norms, social support, and stigma [ 38 ]. Stepwise selection multivariable modeling identified variables statistically independently associated with intention to test by each of three specific HIV testing methods ( Table 1 ; reported previously in [ 38 ]).…”
Section: Methodsmentioning
confidence: 99%